Studi Determinan Perilaku Etis Mahasiswa Akuntansi - Wijayanti, Rita (Jurnal Ekonomi Modernisasi, 2018)
This study aims to obtain empirical evidence of the influence of machiavellian nature, emotional intelligence, spiritual intelligence, and understanding of accountants professional codes of ethics on accounting students' ethical behavior. Sampling is conducted by a purposive sampling method with the criteria of active students who have taken the I and II Auditing courses as well as the Professional Ethics and Business Sharia. A total of 115 questionnaires could be processed further and each question was assessed using a 5-point Likert Scale. Data analysis using multiple linear regression. The results showed that (1) machiavellian nature affect the ethical behavior of accounting students, where the higher the level machiavellian, the higher the tendency to take unethical actions, (2) spiritual intelligence has a positive effect on ethical behavior of accounting students, and (3) understanding of accountants professional codes of ethics has a positive effect on ethical behavior of accounting students. Another variable, namely emotional intelligence has no effect on the ethical behavior of accounting students. However, the four research variables influence the ethical perceptions of accounting students simultaneously. Research findings indicate the importance of ethical and religious content in the college curriculum.